“Senyum Cemerlang, Senyum Pepsodent” A Diachronic Analysis of Language Forms in Pepsodent’s Television Advertisements During Four Decades - Almira Fidela Artha; Fina Syahadatina; Okta Enggiana Pradevi (PAROLE: Journal of Linguistics and Education, 2015)
An advertising always presents messages and invitations either in verbal or non-verbal form which represents a product and also reflects the benefits that is offered to the consumers at the same time. It also happens in atelevision advertisement of toothpaste that is quite popular in Indonesia, named Pepsodent.One of the interesting points in this advertisement is the language changes which occur in every decade (ten years) along with the development of Indonesian society. The data taken are diachronic data started in the 1980s until 2010s by choosing one advertisement for each decade which is considered popular enough in the society.This study analyzes four advertisements that represent four decades to prove that in performing its functions, an advertisement always pays attention to the development of a society as the dominant factor. The results of this study indicate that from sociopragmatics viewpoint, the language used in an advertisement, especially Pepsodent’s television advertisementchanges in the range of tenyears along with the development of the society. Those advertisements show the changes in the meaning and the differences in language selectionin each decade which is influenced by the development of the society. Iklan selalu menghadirkan pesan serta ajakan dalam bentuk verbal maupun non-verbal yangmerupakan representasi sebuah produk dan juga merefleksikan manfaat yang ditawarkan pada saat yang bersamaan. Begitu pula yang terdapat dalam iklan televisi pasta gigi yang cukup populer di masyarakat yaitu Pepsodent.Salah satu hal menarik pada iklan ini adalah perubahan bahasa yang terjadi dalam setiap dekade (sepuluh tahun) seiring dengan berkembangnya masyarakat. Data yang diambil adalah data diakronik mulai tahun 1980an sampai 2010an dengan menggunakan satu iklan yang dianggap cukup populer bagi masyarakat dalam masing-masing dekade. Penelitian ini menggunakan empat iklan yang mewakili empat dekade untuk membuktikan bahwa dalam menjalankan fungsinya, suatu iklan selalu melihat perkembangan masyarakat sebagai kunci dominan. Hasil penelitian ini menunjukkan bahwa dengan kajian sosiopragmatik, bahasa yang digunakan dalam iklan khususnya iklan televisi pasta gigi Pepsodent mengalami perubahan dengan jarak atau rentang waktu persepuluh tahun seiring dengan perkembangan masyarakat. Berdasarkan sudut pandang sosiopragmatik, iklan-iklan tersebut menunjukkan terjadinya perubahan makna serta perbedaan pemilihan bahasa pada tiap dekade yang dipengaruhi oleh perkembangan masyarakat.